2020
DOI: 10.1088/1361-6528/abc388
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and disposable gold nanoparticles-N-doped carbon-modified electrochemical sensor for simultaneous detection of dopamine and uric acid

Abstract: Catalytic and electrocatalytic applications of supported metal nanoparticles are hindered due to an aggregation of metal nanoparticles and catalytic leaching under harsh operations. Hence, stable and leaching free catalysts with high surface area are extremely desirable but also challenging. Here we report a gold nanoparticles-hosted mesoporous nitrogen doped carbon matrix, which is prepared using bovine serum albumin (BSA) through calcination. BSA plays three roles in this process as a reducing agent, capping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Additionally, it can be seen from Table 1 that the detection ranges of CoFe@G/GCE for AA, DA, and UA are comparable to most of the previous work, and shows lower detection limit than other biosensors such as noble metals like Au, [ 54 ] rare earth metals like Tm, [ 55 ] and other carbon‐based sensors. [ 56–58 ] Thus, the new composite material CoFe@G can be a potential candidate for simultaneous detection of AA, DA, and UA.…”
Section: Resultssupporting
confidence: 72%
“…Additionally, it can be seen from Table 1 that the detection ranges of CoFe@G/GCE for AA, DA, and UA are comparable to most of the previous work, and shows lower detection limit than other biosensors such as noble metals like Au, [ 54 ] rare earth metals like Tm, [ 55 ] and other carbon‐based sensors. [ 56–58 ] Thus, the new composite material CoFe@G can be a potential candidate for simultaneous detection of AA, DA, and UA.…”
Section: Resultssupporting
confidence: 72%
“…[10] The in-situ synthesized PdNPs play an essential role in the carbonization process, in which PdNPs showed a catalytic effect in pyrolysis and CO 2 emission to acquire aromatized carbon structure. [11] WK was the best precursor for the synthesis of the N-doped carbon skeleton with the π-π arrangement, which mimics the A-B type polymeric structure; hence, highly susceptible to H + ions. A series of materials were prepared by temperature variation and used for the fabrication of different strip-based solid-state pH sensors.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the in-situ prepared PdNPs of the composite mass catalyzed and accelerated the emission of carbon and nitrogen oxides; thus, resulting in the highly 028201-3 porous and aromatized carbon structure. [11] The surface morphology of PdNPs was investigated by high-resolution TEM (HR-TEM) analysis. Figures 2(a…”
Section: Modification Of Microstructurementioning
confidence: 99%
“…Many studies have been reported for detecting DA and UA in recent years. Metal nanoparticles, 6–8 conducting polymers, 9–11 carbon 12,13 and MXene 14 materials have been used to detect DA and UA electrochemically.…”
Section: Introductionmentioning
confidence: 99%